Environmental Performance Reviews: Serbia - United Nations (United Nations, 2015)
This third review takes stock of the progress made by Serbia in the management of its environment since the country was reviewed in 2007 for the second time. It assesses the implementation of the recommendations contained in the second review. The third review covers policymaking, implementation and the financing of environmental policies and projects. It discusses waste management and the protection of water resources, as well as impacts of and measures to address climate change. The review makes suggestions for strengthening efforts towards a comprehensive and systemic response to sustainable development challenges. The publication is aimed at officials and experts working for public authorities responsible for environmental policy, representatives of civil society, the business community, academia and the media.